2021
DOI: 10.1080/15476286.2021.2012632
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of circular RNA enrichment methods

Abstract: The circRNAs sequencing results vary due to the different enrichment methods and their performance is needed to systematic comparison. This study investigated the effects of different circRNA enrichment methods on sequencing results, including abundance and species of circRNAs, as well as the sensitivity and precision. This experiment was carried out by following four common circRNA enrichment methods: including ribosomal RNA depletion (rRNA – ), polyadenylation and poly (A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…circRNA identification using rRNA-depleted samples yielded not only a higher quantification of transcripts, but also captured more unique transcripts than poly(A)-selected samples. These findings further prove that the RNA-seq selection protocol has a significant impact on the resulting circRNA profiles as previous studies have also observed (47), and brings to question the reliability of previous studies that have used the poly(A)-selection protocol on circRNA detection for biomarker discovery.…”
Section: Resultssupporting
confidence: 80%
“…circRNA identification using rRNA-depleted samples yielded not only a higher quantification of transcripts, but also captured more unique transcripts than poly(A)-selected samples. These findings further prove that the RNA-seq selection protocol has a significant impact on the resulting circRNA profiles as previous studies have also observed (47), and brings to question the reliability of previous studies that have used the poly(A)-selection protocol on circRNA detection for biomarker discovery.…”
Section: Resultssupporting
confidence: 80%
“…We found that the expression of circRNA-5335 increased continuously during the induction of differentiation, suggesting that it may be involved in the adipogenic process. Compared with gDNA, we observed that only the cDNA obtained from the RNase R-treated total RNA showed a specific band corresponding to the backsplice junction fragment [ 40 ], which verified that circRNA-5335 exists in preadipocytes as a circular molecule.…”
Section: Discussionmentioning
confidence: 89%
“…For example, Panda et al applied the same RTP method to enrich circular RNA in HeLa and C2C12 cells by eliminating RNase R resistant transcripts (like U1 snRNA) [ 17 , 18 ]. Shi et al analysed the differences in numbers and biotypes of identified human blood circRNAs between rRNAs removal, polyadenylation followed by RNase R treatment, and the ways that combined these two methods in different orders, respectively [ 19 ]. However, different from cells, tissues consist of specialized cells which can affect the sensitivity of these methods to enrich circRNAs.…”
Section: Discussionmentioning
confidence: 99%